Uma Proposta para Guias Orientadoras para o Design de Interfaces Visuais Não-Diegéticas Dedicadas à Locomoção do Jogador em Realidade Virtual - João Manuel Matos Ferreira (2019)
Currently, there are several types of interfaces for players' locomotion in a virtual space, and there are numerous methods already implemented in products found in the videogames' market. Some interfaces consist of adaptations of the ones found in the traditional format of two-dimensional monitors, while others are experiences designed from scratch for Virtual Reality. However, we are now in a period of experimentation, a time when the players have usufruct of sometimes unstable, sometimes irregular or inadequate game experiences. With this in mind, the possibility of studying this area that is still in constant mutation and in a state of experimentation due to the childhood of this technological environment emerges. In this dissertation, we make a brief historical, technological and design contextualization, to serve as a context to the methodological process on which we address the aforementioned problem. With this in view and in the formulation of a response, we started the elaboration of a framework that focuses on an analytical perspective of non-diegetic interfaces for the locomotion of the player in First Person video games in Virtual Reality environments. In addition to this analytical side, this framework allows us to identify and design different models of non-diegetic interfaces, through the different possible combinations between its components and values, which reveals the same potential in the auscultation of the adequacy of such interface models to the experience that a certain type of game is intended to promote. Keywords: Non-Diegetic Visual Interfaces; Virtual Reality; Video Games; Graphical User Interface Design ; Locomotion in Virtual Spaces.